2023
DOI: 10.3847/1538-4357/acef1f
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Nuclear Parameters Using Gravitational Waves from f-mode Oscillations in Neutron Stars

Bikram Keshari Pradhan,
Dhruv Pathak,
Debarati Chatterjee

Abstract: Gravitational waves (GWs) emanating from unstable quasi-normal modes in neutron stars (NSs) could be accessible with the improved sensitivity of the current GW detectors or with the next-generation GW detectors and, therefore, can be employed to study the NS interior. Assuming f-mode excitation in isolated pulsars with typical energy of pulsar glitches and considering potential f-mode GW candidates for A+ (upgraded LIGO detectors operating at fifth observing run design sensitivity) and Einstein Telescope (ET),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 105 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…The simultaneous measurements of mass and tidal deformability of the NSs from GW measurements play a crucial role in improving the uncertainty in nuclear physics (Güven et al 2020;Traversi et al 2020;Biswas et al 2021;Lattimer 2021;Ghosh et al 2022aGhosh et al , 2022bImam et al 2022;Patra et al 2022;Beznogov & Raduta 2023;Mondal & Gulminelli 2023;Pradhan et al 2023aPradhan et al , 2023bHuang et al 2024). As the ignorance of the f-mode dynamical tides substantially affects the measurement of NS EOS and NS properties, this leads us to question how much bias one would expect on the nuclear parameters constrained using GW observations due to ignorance of f-mode dynamical tides.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous measurements of mass and tidal deformability of the NSs from GW measurements play a crucial role in improving the uncertainty in nuclear physics (Güven et al 2020;Traversi et al 2020;Biswas et al 2021;Lattimer 2021;Ghosh et al 2022aGhosh et al , 2022bImam et al 2022;Patra et al 2022;Beznogov & Raduta 2023;Mondal & Gulminelli 2023;Pradhan et al 2023aPradhan et al , 2023bHuang et al 2024). As the ignorance of the f-mode dynamical tides substantially affects the measurement of NS EOS and NS properties, this leads us to question how much bias one would expect on the nuclear parameters constrained using GW observations due to ignorance of f-mode dynamical tides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications (Sotani 2021;Kunjipurayil et al 2022;Pradhan et al 2022Pradhan et al , 2023b show efforts to estimate nuclear matter parameters using stellar oscillation modes. Pradhan et al (2022) reported how the effective nucleon mass (m å ) at saturation is correlated with the f-mode frequencies for a set of EOSs generated within the RMF formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Future, observations of coalescing BNS events by detectors like LIGO-Virgo-KAGRA, Einstein Telescope [17], and Cosmic Explorer [18] are likely to occur more frequently, enabling a more precise determination of the high-density part of the EoS [19][20][21][22][23][24][25][26][27][28][29][30][31]. The EoS at low densities ρ < 2ρ 0 are constrained by various nuclear physics experiments measuring the bulk properties of finite nuclei such as the nuclear masses, neutron skin thickness in 208 Pb, the dipole polarizability and isobaric analog states as well as the heavy-ion collisions.…”
Section: Introductionmentioning
confidence: 99%